The Transformation from Water to Land Transportation in Samarinda (1980–1998) - Fedro Alvi Hadiid Siregar; Muhammad Azmi; Siti Marfuah; Aulia Rahuma (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2026)
Water transport once played a central role in Samarinda when road connectivity was still limited, especially before the construction of the Mahakam Bridge. This study examines the transformation from water to land transportation in Samarinda during 1980–1998 using the historical method through heuristics, source criticism, interpretation, and historiography. The findings show that the bridge, together with expanding road infrastructure and transport technology, made land travel faster and more efficient than river modes such as ferries, tambangan, and klotok. As a result, everyday mobility shifted toward land routes, river transport patronage declined, and the income of boat operators decreased. The case demonstrates how urban infrastructure reconfigured accessibility, travel behavior, and the socio-economic position of traditional river transport.